A microbiological and clinical review on Corynebacterium kroppenstedtii. (July 2016) - Tauch, Andreas; Fernández-Natal, Isabel; Soriano, Francisco
Highlights: The taxonomy, microbiology, and identification of Corynebacterium kroppenstedtii are reviewed and updated. All published isolations of C. kroppenstedtii are reviewed and analyzed. A comprehensive review of human and animal infections is presented. The possible role of C. kroppenstedtii in granulomatous mastitis is discussed. Antibiotic susceptibility data and detected resistance genes are given and reviewed. Summary: The genus Corynebacterium represents a taxon of Gram-positive bacteria with a high G + C content in the genomic DNA. Corynebacterium kroppenstedtii is an unusual member of this taxon as it lacks the characteristic mycolic acids in the cell envelope. Genome sequence analysis of the C. kroppenstedtii type strain has revealed a lipophilic (lipid-requiring) lifestyle and a remarkable repertoire of carbohydrate uptake and utilization systems. Clinical isolates of C. kroppenstedtii have been obtained almost exclusively from female patients and mainly from breast abscesses and cases of granulomatous mastitis. However, the role of C. kroppenstedtii in breast pathologies remains unclear. This review provides a comprehensive overview of the taxonomy, microbiology, and microbiological identification of C. kroppenstedtii, including polyphasic phenotypic approaches, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, and the use of 16S rRNA gene sequencing. A clinical review presents reported cases, various antimicrobial treatments, antibiotic susceptibility assays, and antibiotic resistance genes detected during genome sequencing. C. kroppenstedtii must be considered a potential opportunistic human pathogen and should be identified accurately in clinical laboratories.